Retos de la gestión pública: presupuesto por resultados y rendición de cuentas - Franciskovic, Jubitza (Universidad ESAN. ESAN Ediciones, 2013)
Document searches draw attention to the need to discuss, theoretically and practically, the challenges that must be faced by public administration in the management of preparing a budget by results and accountability, particularly when taking into account the useful tools in the process of ensuring “good government”. To do this, a conceptual analysis of both tools was performed. Firstly, the management by results approach is presented, along with the challenges that this new framework involves for the public administration in relation to the optimisation of the use of public resources, to ensure a transparent and equitable process and to improve the performance of public bodies, becoming the basis for better accountability (the second aspect analysed in the document). Accountability becomes a challenge, on being an effective means of monitoring and sanctions between society and government, through which the public servants have to respond, explain and justify their actions, subjected to an ethical and juridical order, to the completing of objectives. It is here where the direct participation by the civil society is fundamental for the evaluation of the results. The document analyses these concepts at a time when our country has the improvement in the quality of public spending as a national priority. Thus, the results approach in the budget preparation has to be considered, by those responsible for economic policy, such as a key mechanism to achieve this, and in turn accountability is particularly linked, to the push that it attempt to give to social policy, as an important element in the administration for the management of public funds, which can help to ensure the effectiveness and transparency of these processes.

El documento busca llamar la atención sobre la necesidad de discutir –teórica y prácticamente– los desafíos que deben ser asumidos por la gestión pública en el manejo de la elaboración presupuestal por resultados y la rendición de cuentas, especialmente considerándolas herramientas útiles en el proceso de asegurar un «buen gobierno». Para ello, se ha realizado un análisis conceptual de ambas herramientas. Primero, se presenta el enfoque de gestión por resultados y los retos que implica este nuevo marco para la gestión pública en relación a la optimización del uso de recursos públicos, la garantía de un proceso transparente y equitativo y la mejora en el desempeño de las entidades públicas, convirtiéndose en la base para una mejor rendición de cuentas –segundo aspecto analizado en el documento–. La rendición de cuentas se convierte en un desafío al constituirse como medio efectivo de vigilancia y sanción entre la sociedad y el gobierno, a través del cual los funcionarios públicos deben responder, explicar y justificar sus actos, sujetos a un orden jurídico ético y al cumplimiento de objetivos. Es aquí donde la participación directa de la sociedad civil es fundamental para la evaluación de los resultados. El documento analiza estos conceptos en un momento en el que nuestro país tiene como prioridad nacional la mejora de la calidad del gasto público. Por eso, el enfoque de resultados en la elaboración presupuestal se ha considerado, por los responsables de la política económica, como un mecanismo clave para su consecución, y a su vez la rendición de cuentas se vincula –particularmente– con el impulso que se pretende dar a la política social, como un elemento de importancia en la gestión para el manejo de fondos públicos, que puede ayudar a garantizar la eficacia y transparencia de estos procesos.
Keywords: New public administration; Participatory budget; Nueva gestión pública; Budget by results; Presupuesto participativo; Presupuesto por resultados; Accountability; Rendición de cuentas; https://purl.org/pe-repo/ocde/ford#5.02.04